Fluorescent probes for proteolysis: Tools for drug discovery - Neefjes, Jacques (Nat Rev Drug Discov, 2004)
Cells contain numerous proteases, which are found at many different locations. These proteases recognize an even larger number of different substrates and are involved in almost every process in the cell. Aberrations in proteolysis are linked to a plethora of diseases, such as cancer, inflammation, arteriosclerosis, neurodegeneration and infection. Because of their well-defined chemistry and key role in pathologies, proteases have been important targets for drug development. Recent progress in the development of fluorescent probes has opened up the possibility of visualizing protease activities in the natural environment of the cell. We will describe various strategies to follow protease activities in cells and organisms.